Quantifying metal artefact reduction using virtual monochromatic dual-layer detector spectral CT imaging in unilateral and bilateral total hip prostheses. Issue 88 (March 2017) - Wellenberg, R.H.H.; Boomsma, M.F.; van Osch, J.A.C.; Vlassenbroek, A.; Milles, J.; Edens, M.A.; Streekstra, G.J.; Slump, C.H.; Maas, M.
Highlights: Dual-layer detector CT reduces metal artefacts at high monochromatic energies (keV). 130 keV images were optimal based on quantitative analysis on CNRs. Optimal keVs varied from 74 to 150 keV for different hip prostheses configurations. The Titanium alloy resulted in less severe artefacts compared to the Cobalt alloy. Severe metal artefacts, caused by extensive photon-starvation, were not reduced. Abstract: Purpose: To quantify the impact of prosthesis material and design on the reduction of metal artefacts in total hip arthroplasties using virtual monochromatic dual-layer detector Spectral CT imaging. Methods: The water-filled total hip arthroplasty phantom was scanned on a novel 128-slice Philips IQon dual-layer detector Spectral CT scanner at 120-kVp and 140-kVp at a standard computed tomography dose index of 20.0 mGy. Several unilateral and bilateral hip prostheses consisting of different metal alloys were inserted and combined which were surrounded by 18 hydroxyapatite calcium carbonate pellets representing bone. Images were reconstructed with iterative reconstruction and analysed at monochromatic energies ranging from 40 to 200 keV. CT numbers in Hounsfield Units (HU), noise measured as the standard deviation in HU, signal-to-noise-ratios (SNRs) and contrast-to-noise-ratios (CNRs) were analysed within fixed regions-of-interests placed in and around the pellets. Results: In 70 and 74 keV virtual monochromatic images the CT numbers of the pellets were similar to 120-kVp and 140-kVp polychromatic results, therefore serving as reference. A separation into three categories of metal artefacts was made (no, mild/moderate and severe) where pellets were categorized based on HU deviations. At high keV values overall image contrast was reduced. For mild/moderate artefacts, the highest average CNRs were attained with virtual monochromatic 130 keV images, acquired at 140-kVp. Severe metal artefacts were not reduced. In 130 keV images, only mild/moderate metal artefacts were significantly reduced compared to 70 and 74 keV images. Deviations in CT numbers, noise, SNRs and CNRs due to metal artefacts were decreased with respectively 64%, 57%, 62% and 63% (p < 0.001) compared to unaffected pellets. Optimal keVs, based on CNRs, for different unilateral and bilateral metal hip prostheses consisting of different metal alloys varied from 74 to 150 keV. The Titanium alloy resulted in less severe artefacts and were reduced more effectively compared to the Cobalt alloy. Conclusions: Virtual monochromatic dual-layer Spectral CT imaging results in a significant reduction of streak artefacts produced by beam-hardening in mild and moderate artefacts by improving CT number accuracy, SNRs and CNRs, while decreasing noise values in a total hip arthroplasty phantom. An optimal monochromatic energy of 130 keV was found ranging from 74 keV to 150 keV for different unilateral and bilateral hip prostheses consisting of different metal alloys.